The Influence of Creativity and Family Environment on Entrepreneurial Intention Mediated by Self-Efficacy in Management Students S1 Meruya Campus in the 2021/2022 Academic Year, Mercu Buana University - Saputra, Heri; Johanes, Singmin (Journal of Advances in Accounting, Economics, and Management, 2024)
This study aims to determine the effect of Creativity and Family Environment on Entrepreneurial Intention Mediated by Self-Efficacy in Undergraduate Management Students of Meruya Campus in the 2021/2022 academic year of Mercu Buana University. The population of this study were students of Universitas Mercu Buana S1 Management Study Program in 2021/2022, with a sample size of 247. The data analysis method uses purposive random sampling using Partial Least Square (Smart-PLS). The results of the study found that creativity has a significant effect on entrepreneurial intention, creativity has a significant effect on self-efficacy, family environment has no effect on entrepreneurial intention, family environment has a significant effect on self-efficacy, self-efficacy has a significant effect on entrepreneurial intention, self-efficacy significantly mediates creativity on entrepreneurial intention, and self-efficacy significantly mediates family environment on entrepreneurial intention.